Efektivitas Penerapan Model Pembelajaran Jigsaw Berbantuan Crossword Puzzle Terhadap Keaktifan Siswa Sekolah Dasar - Feni Nabila Putri; Syailin Nichla Choirin Attalina (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
This study was motivated by the low learning activity of fifth-grade students at SDN 3 Sekuro, which was assumed to be caused by learning models that were less varied and did not sufficiently involve students in the learning process. The purpose of this study was to determine the effectiveness of applying the Jigsaw learning model assisted by Crossword Puzzle media on students’ learning activeness in the IPAS subject. The research employed a quantitative approach with a one-group pretest-posttest design. The research instrument consisted of a learning-activeness questionnaire that had been tested to have it validated by an expert validator to ensure its feasibility. The results showed that the average score of students’ learning activeness increased from 65 in the pretest to 83 in the posttest, with a Paired Sample T-Test significance value of 0.000 (p < 0.05). This indicates a significant difference in students’ learning activity before and after the implementation of the Jigsaw learning model assisted by Crossword Puzzle media. This study suggests that the implementation of the Jigsaw learning model assisted by Crossword Puzzle media is effective in IPAS learning because it can enhance students’ active participation, strengthen group collaboration, and create more meaningful and enjoyable learning experiences.